2022
DOI: 10.1155/2022/2651062
|View full text |Cite
|
Sign up to set email alerts
|

Combined Application of Grid Body Surface Locator and Preemptive Analgesia in Daytime Vertebroplasty

Abstract: Objective. To explore the clinical advantages of grid body surface locator combined with preemptive analgesia in the treatment of osteoporotic lumbar fractures in daytime vertebroplasty. Methods. A retrospective study was conducted on 120 patients who underwent lumbar vertebroplasty in the Department of Orthopedics of General Hospital of Northern Theater Command from January 2017 to January 2020. According to the preoperative planning and analgesic mode of treatment, they were divided into the daily operation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In previous studies, preoperatively designed PVP involved less radiation, a shorter operation and fewer complications than traditional PVP [14,15]. Our previous research has also indicated that unilateral PKP using a novel 3D-printed guide device is a safe and effective technique for OVCFs [21].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In previous studies, preoperatively designed PVP involved less radiation, a shorter operation and fewer complications than traditional PVP [14,15]. Our previous research has also indicated that unilateral PKP using a novel 3D-printed guide device is a safe and effective technique for OVCFs [21].…”
Section: Discussionmentioning
confidence: 90%
“…However, these technologies are expensive and/or have high technical requirements; thus, they cannot be widely used in primary hospitals. We have given much attention to the preoperative planning [14,15] and 3D printing technologies [16][17][18][19][20] used in percutaneous vertebroplasty (PVP)/PKP, and previous studies have shown that PVP with preoperative puncture design is not only reasonably safe and effective for OVCFs but also involves less radiation, shorter operation times and fewer complications than traditional PVP [14,15]. Our research has indicated that unilateral puncture using a novel 3D-printed guide device is a safe and effective technique for OVCFs and is associated with fewer intraoperative fluoroscopy exposures and shorter operation times [21].…”
Section: Introductionmentioning
confidence: 99%